Spatial variability of selected soil properties in relation to land use and slope position in Gelana sub-watershed, Northern highlands of Ethiopia. (4th May 2018) - Miheretu, Birhan Asmame; Yimer, Assefa Abegaz
Abstract: Land degradation resulting from land-use changes and soil erosion has been a serious environmental problem in Ethiopia. This study addressed the effects of land use and slope position on soil physical and chemical properties in the Gelana sub-watershed, Northern highlands of Ethiopia. A total of 63 soil samples were collected and analyzed using a two-way ANOVA. Results showed that clay, soil pH, soil organic matter, total nitrogen, cation exchange capacity, and exchangeable base contents of the cultivated land were significantly ( p  < 0.001) lower than those of the forest land, while soil bulk density, available phosphorous, and percentage base saturation were higher for cultivated land than forest land. In general, soil fertility declines as land use changes from forest to grazing and cultivated lands. Sand, clay, bulk density, soil pH, organic matter, total nitrogen, carbon:nitrogen ratio, available phosphorous, cation exchange capacity, exchangeable cations, and percentage base saturation showed significant variation due to slope position differences. Therefore, the study reinforces the need for integrated watershed management for sustainable agricultural production in the study area.